Estudio geológico geotécnico del ramal 4 para la rehabilitación del canal de riego en el sector “El Tingo” de la parroquia “Amaluza”, perteneciente al cantón Espíndola, provincia de Loja - Ecuador. - Naranjo Oviedo, Enma Gabriela (2018)
The present thesis research entitled "GEOTECHICAL GEOGRAPHIC STUDY OF RAMAL 4 FOR THE REHABILITATION OF THE IRRIGATION CHANNEL IN THE SECTOR “EL TINGO” IN THE PARISH “AMALUZA", BELONGING TO THE CANTON ESPÍNDOLA, PROVINCE OF LOJA - ECUADOR" is focused on describing the properties of the materials from the geological, geotechnical and hydrological points of view in the sector of “El Tingo”. After, all the basic information was recompiled, it proceeded to carry out the topographic survey in detail of the study area, the total area of study is 62.5 hectares. The geological formation that makes up the study area is the Sacapalca Formation and the geological units that belong to it are: Changaimina Unit, Ingenio Unit and the Rio Guayuco Unit. The corresponding geomorphological units are: mountainous relief, high-pitched relief, middle-relief and alluvial colluvium. From the direct methods: The pits allowed to describe the texture, color, humidity, and consistency; and the Standard Penetration Test allowed to determine classification properties (SUCS), by obtaining: SUCS: SC, correspond to high plasticity clays; for SPT 1 and SC, CL, correspond to clayey sand and clay of low plasticity, for SPT 2. The carrying capacity, density, cohesion and internal friction angle were obtained by relating the NSPT values which ranges go from 28 strokes in the softest areas to 48 strokes in areas of greater hardness. The geophysical tests: the vertical electric probes allowed to obtain a range of values of apparent resistivity, ranging from 8.7 Ω.ma> 1000 Ω.m, the first corresponds volcanic material with high permeability (volcanic lava) with high content of humidity and the second corresponds to very compact volcanic Tobas. In addition, the evaluation of rock masses was carried out by using the Bienawski method, the result allows to classify slopes of good quality at the beginning of branch 4 and bad quality at the end of the same.